Mechanisms for appropriating innovations related to Software used by Fintechs: a systematic mapping of the state of the art - Silva, Reinaldo Eustaquio; Nunes, Maria Augusta S. N.; Machado, Rita Pinheiro (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2022: Anais do XVIII Simpósio Brasileiro de Sistemas de Informação, 2022)
The Software segment has great potential for accumulating technological innovations, especially those produced by Fintechs. In this context, protection via Intellectual Property (IP) of new technologies has a direct impact on the three basic dimensions of Information Systems (IS): Technological, Human and Organizational. Protecting innovations via IP (Technological dimension) has been a great challenge and the difficulties are associated with new business models (Organizational dimension) that demand efforts (Human dimension) to identify the assets to be protected. This article aims to identify IP appropriation mechanisms to protect software-related innovations produced by Fintechs, as well as analyze the context of appropriation from the perspective of IS dimensions. The Systematic Literature Mapping (SLM) method was used with a descriptive character. The analysis of the results was carried out with a quantitative approach. This work was conceived according to the Theory of Diffusion of Innovations, mainly with regard to the diffusion of knowledge produced, protected via IP and introduced in the market. The results revealed that Fintechs appropriate their innovations via IP; however, they face difficulties associated with the complex characteristics of the Software itself, such as its intangible nature. The main contribution of the article is to propose an analysis of how the appropriation of technological innovations via IP impacts the human and organizational dimensions of Fintechs, through the Management of their IP assets. Thus, it aims to offer new reflections to broaden the understanding of the proposed theme within the context of the IS.